Amino acid supplementation in mitochondrial aminoacyl-tRNA synthetase defects: two case reports of tyrosine supplementation in YARS2-associated disease and a review of the literature - Ferrera, Giulia; Segre, Giorgia; Lamantea, Eleonora; Ghezzi, Daniele; Rivelli, Marta; Ardissone, Anna (Frontiers in Pediatrics, 2025)
BackgroundMitochondrial diseases (MDs) caused by pathogenic variants in aminoacyl-tRNA synthetase (ARS) genes, either cytosolic (ARS1) or mitochondrial (ARS2), are rare and clinically diverse. YARS2 deficiency causes myopathy, lactic acidosis, and sideroblastic anemia (MLASA2). No treatments exist, although targeted amino acid (AA) supplementation could function as a possible therapy, as many ARS variants retain partial activity. While benefits have been reported in several ARS1 disorders, evidence in ARS2 diseases, including YARS2 deficiency, remains limited.MethodsWe report two siblings with genetically confirmed MLASA2 due to homozygous YARS2 variants who received oral tyrosine for 12 months. Clinical, biochemical, cardiac, and thyroid safety assessments were performed at baseline and follow-up. Standardized measures tracked motor function, symptoms, and quality of life. A systematic review of AA supplementation in ARS2 deficiencies was also conducted.ResultsTyrosine was well tolerated. The more severely affected sibling showed improvements in motor function, endurance, and quality of life, with modest prolongation of transfusion intervals. The milder sibling reported increased energy and functional gains. Cardiac function remained stable. Literature review revealed only five prior ARS2 cases treated with AA supplementation, with variable outcomes.ConclusionYARS2-related MLASA2 is a severe disorder associated with high morbidity and premature mortality. No spontaneous recovery has been reported, supporting tyrosine as the likely driver of observed improvements. No cardiac or thyroid toxicities were detected during treatment. Prior reports, although limited, support the feasibility of this treatment. Our findings suggest tyrosine is a promising candidate therapy in YARS2 deficiency; larger multicenter studies are needed to validate our data.